Investigation of calpastatin (CAST) gene polymorphism in Norduz sheep by PCR-RFLP method - Yilmaz, O; Çak, B; Demirel, AF (Journal of the Hellenic Veterinary Medical Society, 2024)
The objective of this research was to determine polymorphism in the calpastatin (CAST) gene in a group of 102 Norduz sheep. Polymorphism was identified using the PCR-RFLP technique. The amplified PCR product with the length of 622 bp was digested with restriction enzymes MspI. It was found that the M and N alleles were present in CAST/MspI locus, their frequency being 78.43 and 21.57%, respectively. Homozygous for the M allele (MM) produced two bands of 336 and 286 bp. Three bands of sizes 622, 336 and 286 bp were seen in case of heterozygous genotype (MN), and homozygous for the N allele (NN) showed a 622 bp band only. The frequencies of homozygous MM, heterozygous MN and homozygous NN genotype were 64.7, 27.5 and 7.8%, respectively. The genotype frequency distributions were in Hardy-Weinberg Equilibrium. In conclusion, the current study is the first study on genotyping of the CAST gene in Norduz sheep. The CAST gene was polymorphic in Norduz sheep. In the CAST gene, the predominant allele in the population was M, with a frequency of 78.43%. The MM and MN genotypes represented 92.2% of the genotype frequencies. The MM genotype was the most common, and NN genotype had the lowest genotype frequency. These results also indicate that in order to be used the polymorphism in the exon 1C/1D region of the CAST gene as a biomarker in Norduz sheep, primarily, association studies with economic traits should be performed.